An Evolutionarily Conserved Mechanism of Calcium‐Dependent Neurotoxicity in a Zebrafish Model of Fetal Alcohol Spectrum Disorders. (11th February 2014) - Flentke, George R.; Klingler, Rebekah H.; Tanguay, Robert L.; Carvan, Michael J.; Smith, Susan M.
<x xml:space="preserve">Abstract</x> Background Fetal alcohol spectrum disorders (FASD) are a leading cause of neurodevelopmental disability. Nonhuman animal models offer novel insights into its underlying mechanisms. Although the developing zebrafish has great promise for FASD research, a significant challenge to its wider adoption is the paucity of clear, mechanistic parallels between its ethanol (EtOH) responses and those of nonpiscine, established models. Inconsistencies in the published pharmacodynamics for EtOH‐exposed zebrafish, alongside the use of comparatively high EtOH doses, challenge the interpretation of this model's clinical relevance. Methods To address these limitations, we developed a binge, single‐exposure model of EtOH exposure in the early zebrafish embryo. Results Brief (3‐hour) EtOH exposure is sufficient to cause significant neural crest losses and craniofacial alterations, with peak vulnerability during neurogenesis and early somitogenesis. These losses are apoptotic, documented using TUNEL assay and secA5‐YFP‐reporter fish. Apoptosis is dose dependent with an EC50 = 56.2 ± 14.3 mM EtOHint, a clinically relevant value within the range producing apoptosis in chick and mouse neural crest. This apoptosis requires the calcium‐dependent activation of CaMKII and recapitulates the well‐described EtOH signaling mechanism in avian neural crest. Importantly, we resolve the existing confusion regarding zebrafish EtOH kinetics. We show that steady‐state EtOH concentrations within both chorion‐intact and dechorionated embryos are maintained at 35.7 ± 2.8% of EtOHext levels across the range from 50 to 300 mM EtOHext, a value consistent with several published reports. Equilibrium is rapid and complete within 5 minutes of EtOH addition. Conclusions The calcium/CaMKII mechanism of EtOH's neurotoxicity is shared between an amniote (chick) and teleost fish, indicating that this mechanism is evolutionarily conserved. Our data suggest that EtOHext concentrations >2% (v/v) for chorion‐intact embryos and 1.5% (v/v) for dechorionated embryos have limited clinical relevance. The strong parallels with established models endorse the zebrafish's relevance for mechanistic studies of EtOH's developmental neurotoxicity.